The Effect of Participatory Budgeting on Budget Slack is Moderated by Information Asymmetry, Budget Emphasis, Organizational Commitment and Ethical Considerations - Mega Maranda Suwandi; Nur Fadjrih Asyik; Ikhsan Budi Riharjo (Journal of Social Research, 2023)
Public sector organizations are established with the aim of providing maximum service to the community. The public sector in order to realize its services, is expected to determine strategies in developing the quality and quantity of its services to the community. The purpose of this study is to measure and provide empirical evidence of the effect of participatory budgeting on budget slack moderated by 4 moderation variables namely information asymmetry, budget emphasis, organizational commitment and ethical considerations. This research is quantitative research using primary data in the form of questionnaire data. The population taken at SKPD Kota Surabaya in the Administration of Development and Procurement of Goods/Services of Surabaya City. The technique used to analyze the data uses multiple regression tests and MRA (Moderated Regression Analysis). This study proves that, participatory budgeting has a significant positive effect on budget slack, while information asymmetry, budget emphasis, organizational commitment, ethical considerations do not moderate the relationship of participatory budgeting to budget slack in the SKPD of the Development Administration and Procurement of Goods/Services of Surabaya City.